2012
DOI: 10.1111/joor.12016
|View full text |Cite
|
Sign up to set email alerts
|

Disc displacement within the human temporomandibular joint: a systematic review of a ‘noisy annoyance’

Abstract: To describe the scientific literature about the diagnosis, prevalence, aetiology, natural course and possible treatment modalities of disc displacements within the temporomandibular (TM) joint. PubMed was searched for specific indexing terms. The search yielded 1211 papers. After screening according to title and abstract, 695 papers were excluded, and after full-text reading, 107 papers remained. Hand-searching of the reference lists resulted in an extra 47 papers. Thirteen studies, published since the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
77
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 140 publications
4
77
0
3
Order By: Relevance
“…A common subgroup of TMD is the disc displacement with reduction (DDR), manifesting with TMJ noise during jaw movement or function, with a prevalence ranging from 18% to 35% of the population. (Naeije, Te Veldhuis, Te Veldhuis, Visscher & Lobbezoo, 2013;Schiffman et al, 2014). TMD patients with both DDR diagnosis and pain as well as complaints of mandibular function impairment are common among those that seek treatment (Ferreira et al, 2014;Santana-Mora et al 2014;Tartaglia, Lodetti, Paiva, De Felicio & Sforza, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A common subgroup of TMD is the disc displacement with reduction (DDR), manifesting with TMJ noise during jaw movement or function, with a prevalence ranging from 18% to 35% of the population. (Naeije, Te Veldhuis, Te Veldhuis, Visscher & Lobbezoo, 2013;Schiffman et al, 2014). TMD patients with both DDR diagnosis and pain as well as complaints of mandibular function impairment are common among those that seek treatment (Ferreira et al, 2014;Santana-Mora et al 2014;Tartaglia, Lodetti, Paiva, De Felicio & Sforza, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…17 According to Naeije, 18 a small number of patients (12-30%) demonstrate the classic symptoms of a closed lock because DDWR often and quickly develops into the chronic stage. However, the long-term prognosis of ID is not really known, [18][19][20] even if an undesirable natural course seems to be relatively uncommon. 17,18,[21][22][23][24] Naeije also showed that DD develops during childhood and adolescence, and sometimes DD may limit condylar growth and consequently be correlated with retrognathia and facial asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long-term prognosis of ID is not really known, [18][19][20] even if an undesirable natural course seems to be relatively uncommon. 17,18,[21][22][23][24] Naeije also showed that DD develops during childhood and adolescence, and sometimes DD may limit condylar growth and consequently be correlated with retrognathia and facial asymmetry. 18,25,26 This is why it is important to improve the clinical diagnosis of DDWR, even under asymptomatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Disc displacement is one of the most frequent temporomandibular disorders, with reported prevalence ranging from 18% to 35% in general population ( 9 ). In disc displacement with reduction the disc is anteriorly displaced in the closed mouth position and reverts to a normal superior position during opening ( 10 ).…”
Section: Introductionmentioning
confidence: 99%